Sustainable Solid Waste Management from the Perspective of the Circular Economy: Alternatives and Solutions for Urban Development - Souza , Ivone Borges (ANAP Brazil, 2025)
Objective – This study aims to analyze the challenges and opportunities of implementing the circular economy in urban solid waste management in the Metropolitan Region of Goiânia. The focus is on the role of waste pickers’ cooperatives, available infrastructure, current public policies, and technological innovation possibilities to improve the system. Methodology – The research adopted a mixed approach, combining bibliographic and documentary review with the collection of primary data through questionnaires applied to public managers, cooperative representatives, and experts in the field. Additionally, secondary data from institutional sources such as IBGE, ABRELPE, and municipal environmental departments were analyzed to map the current waste management landscape in the region. Originality/relevance – This study fills a theoretical gap by integrating the analysis of structural challenges in waste management with the application of the circular economy in a metropolitan context. The research highlights the need for more robust public policies, infrastructure investments, and incentives to strengthen waste pickers’ cooperatives as key players in the recycling chain. Results – The findings indicate weaknesses in selective collection and recycling infrastructure, low public adherence to sustainable practices, and the precarization of waste pickers’ cooperatives. Additionally, the lack of investments in reuse technologies and the absence of economic incentives hinder the transition to a more efficient and sustainable model. Theoretical/methodological contributions – The study proposes strategies to strengthen the circular economy in urban solid waste management, emphasizing the importance of regulatory financial incentives, infrastructure improvements, and cooperative training. The adopted methodology, based on a combination of documentary analysis and empirical research, can be replicated in other urban contexts. Social and environmental contributions – The research underscores the importance of environmental education as a key factor in increasing recycling rates and engaging society in the circular economy. Moreover, it highlights the need for integrated actions between government, the private sector, and civil society to promote innovation, operational efficiency, and social inclusion in the waste management sector.